2017
DOI: 10.1016/j.jad.2016.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing Bipolar Disorder and Schizophrenia: A cross-diagnostic cluster analysis of cognitive phenotypes

Abstract: This study identified two clusters with shared cognitive phenotype profiles that were not proxies for clinical diagnoses. The finding of better social cognitive performance of BD patients than SZ patients in the Lowe cluster suggest that relatively preserved social cognition may be important to identify disease process distinct to each disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 60 publications
4
28
0
1
Order By: Relevance
“…Impairments have been reported in many cognitive domains, including verbal learning and memory, verbal fluency, working memory, processing speed, and executive function (Bilder et al, 2002; Hill et al, 2013, 2004a; Saykin et al, 1994). Similar neuropsychological deficits, albeit less severe, are reported in other psychotic disorders (Hill et al, 2013, 2009, 2008; Lee et al, 2016). Cognitive impairment relates directly to functional outcomes in patients such as psychosocial skill acquisition, performing daily activities, and vocational attainment and contributes to poor quality of life (Green et al, 2000; Leifker et al, 2009).…”
Section: Introductionsupporting
confidence: 72%
“…Impairments have been reported in many cognitive domains, including verbal learning and memory, verbal fluency, working memory, processing speed, and executive function (Bilder et al, 2002; Hill et al, 2013, 2004a; Saykin et al, 1994). Similar neuropsychological deficits, albeit less severe, are reported in other psychotic disorders (Hill et al, 2013, 2009, 2008; Lee et al, 2016). Cognitive impairment relates directly to functional outcomes in patients such as psychosocial skill acquisition, performing daily activities, and vocational attainment and contributes to poor quality of life (Green et al, 2000; Leifker et al, 2009).…”
Section: Introductionsupporting
confidence: 72%
“…In fact, cluster analysis studies have reported within‐group heterogeneity in the cognitive performance of individuals with BD, suggesting the existence of subgroups based on performance. While some authors divide them into similar to the HC range and selective cognitive impairment (representing almost one‐third of the sample), 66,67 others divide the impaired group into selective cognitive impairment (modest deficits on only a subset of domains) and global severe impairment (deficit across most of the cognitive domains) 68‐71 …”
Section: Discussionmentioning
confidence: 99%
“…Cluster analysis is a statistical technique that identifies subgroups in wider multidimensional or heterogeneous data, which application to multifaceted diseases, such as major depression, could help dissect disease heterogeneity, advancing diagnostic criteria, and improving treatment plans 34 36 .…”
Section: Introductionmentioning
confidence: 99%